O Minist??rio P??blico e o controle externo da atividade de pol??cia judici??ria militar: em busca de uma desej??vel efetividade - Duarte, Ant??nio Pereira (2016)
This dissertation deals with the external control of all aspects of police activity, with particular emphasis on control of the military judicial police activity and the need to ensure their full efficiency. Within this perspective, begins by explaining the bodies responsible for constitutional activity of National Defence and Public Security, showing then the military justice system defined by the Federal Constitution of 1988 for the application of standards to military criminal law, which highlighted judicial courts and prosecutors with a high degree of expertise. Deepens the discussion on the Judicial Military Police model adopted in Brazil to promote the military criminal investigations, revealing its shortcomings and the indispensability of his readaptation, celing by a lack of professionalization of charge by carrying out the assignment. Under this framework, ends by demonstrating that all administrative activity, including the judicial police activity, is subject to the constitutional principle of efficiency, which projects into various pecularities of investigative actions, notably in productivity, quality and speed. This study also advances on constitutional and infra-constitutional design of the external control of police activity in its different forms of expression, indicating the possibility that the Military Prosecutor had to be more effective control of the investigations carried out by the Military Judicial Police, which there always be guided by the highest efficiency and the unrestricted respect for fundamental rights and guarantees. The final approach is suggesting solutions to improve the profile of the military judicial police activity - proposing its institutionalization; as well as the profile of the external control exercised by the Military Public Ministry, whose demands more widened especially with the advent of the National Council of the Public Ministry as external control agency, which has worked for the improvement of the national Public Ministry.